DESIGN AND DEVELOPMENT SYSTEM OF ELECTRONIC CANDLE BASED ON MICROCONTROLLER - Yeli Fitri Lianuari; Budi Usmanto (STMIK Pringsewu Lampung, 2017)
In this paper is described how the assembly process of designing and developing a series of inflatable candles microkontroller. The series based on electronics is a simple circuit that utilizes condenser microphone as a sensor. The use of these components are suitable for use in an application circuit electronic candles where the workings of this series starts from LEDs that analogous to wax and then lit using a pushbutton that analogy as lighters, and a flame from the LED can be extinguished by blowing. The concept of this series is simple but could be developed into a series of more innovative and interesting. One development is to add the output of the LED running that made candles burn more lively and interesting. Running LED of this circuit works by using a transistor as a switch that controls power of Az IC 368 and IC Az 418 M J. To simplify the development process, combination of a series of electronic candles with LED running can be simulated using the software Livewire and Proteus. Results of designing and developing a tool is not a new thing or that have not been found but the result of this achievement can be a source of inspiring in the world of electronics that can later be developed further so that it becomes a result of more recent example, lights out with once pat.